2018
DOI: 10.1111/ane.13037
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D supplementation and neurofilament light chain in multiple sclerosis

Abstract: Objectives The effect of vitamin D supplementation on the disease course of multiple sclerosis (MS) is not established. Neurofilament light chain (NFL) is a sensitive marker of axonal degeneration. The aim of this study was to establish whether high‐dose vitamin D supplementation reduces serum levels of NFL. Materials and Methods We have performed a 96 weeks placebo‐controlled randomized study of weekly supplementation with 20 000 IU vitamin D3 in 71 patients with relapsing remitting MS (RRMS). Serum levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 34 publications
6
26
1
Order By: Relevance
“…However, our results do not support an effect of rising 25(OH)D levels driven mainly by seasonal alterations in UVR exposure on axonal degeneration in RRMS, as measured by serum NfL levels. This is in line with the finding of no effect of high-dose oral vitamin D 3 supplementation on serum NfL levels in RCTs among RRMS patients with DMT (10,11).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…However, our results do not support an effect of rising 25(OH)D levels driven mainly by seasonal alterations in UVR exposure on axonal degeneration in RRMS, as measured by serum NfL levels. This is in line with the finding of no effect of high-dose oral vitamin D 3 supplementation on serum NfL levels in RCTs among RRMS patients with DMT (10,11).…”
Section: Discussionsupporting
confidence: 90%
“…Due to the northern location of Norway, vitamin D status varies substantially between winter (November to March) and summer (May to September). We have earlier seen a trend for a reduction in serum NfL levels among RRMS patients without DMTs on vitamin D supplementation (10). Moreover, we have shown that introduction of IFN-β therapy reduces NfL levels in the current patient cohort (5).…”
Section: Relationship Between Serum Levels Of 25(oh)d and Nflmentioning
confidence: 57%
See 2 more Smart Citations
“…Cortical lesions and gray matter loss are more strongly associated with cognitive decline than white matter lesions, 4 but ultimately, we cannot evaluate from NfL elevations only which pathology was driving the results. Intriguingly, vitamin D supplementation was associated with decreased NfL levels in a 2-year randomized clinical trial among untreated patients with MS. 45 In another study, smoking was linked to brain atrophy, 19 which is, in turn, related to neuroaxonal injury and cognitive impairment. 5 Our findings add to the evidence that NfL may be a promising biomarker for clinical MS research.…”
Section: Discussionmentioning
confidence: 98%